THE ECTHR’S LEGAL POSITION ON THE UNDERSTANDING OF THE PROHIBITION OF FORCED LABOR AS STANDARDS FOR THE PROTECTION OF HUMAN RIGHTS - VAKARIUK, LIUDMYLA (Ehrlich’s Journal, 2023)
The article emphasizes that Ukraine is a party to the Convention for the Protection of Human Rights and Fundamental Freedoms, the International Covenant on Civil and Political Rights, the ILO Conventions on Forced or Compulsory Labor and the Abolition of Forced Labor. In this regard, Ukraine is obliged to eradicate all forms of forced or compulsory labor in all spheres of life, to prevent forced labor in both the public and private sectors, and to provide effective redress to those whose rights have been violated. It is emphasized that forced labor and trafficking in human beings are not only a gross violation of human rights and employee’s rights, but also the antithesis of decent work. Freedom from forced labor is one of the basic labor rights that should be properly promoted and protected. Analysis of the legal positions of the European Court of Human Rights on the prohibition of forced labor will assess the state and prospects for improving the judicial protection of labor rights, their applicability in domestic practice. It is emphasized that the case law of the European Court of Human Rights is an official form of interpretation of fundamental labor rights of every person, enshrined and guaranteed by the European Convention on Human Rights, which is part of national law and a source of legal regulation and enforcement in Ukraine. As a source of labor law, ECtHR decisions directly affect labor relations, their content, emergence, change or termination, contribute to legal stability and orderly development of the practice of application of the Convention. It is argued that the European Convention on Human Rights contains only the prohibition of forced labor, which in modern economic conditions can not cover all cases of violations of labor rights, the need for protection of which objectively exists. In recent years, there has been a tendency in the activities of the ECtHR to expand the interpretation of the rules of the ECHR in order to protect the rights and interests of the individual. For labor law, the extension of the content of the provisions of the Convention by the European Court of Human Rights is of particular importance, as it allows to increase the range of issues on which it is possible to seek protection of labor rights.